The effects of subdermal hormonal contraceptive implant on health indices. A preliminary report - Zainuddin, Ahmad Murad (The Faculty of Medicine, International Islamic University Malaysia, 2007)
Subdermal etonogestrel implant (Implanon®) is the newest, long term contraceptive implant which has recently been made available to Malaysian women. This prospective study was conducted to determine the effects on selected health indices among 42 women who had consented to Implanon® as their choice of contraception. Health indices were checked prior to Implanon® insertion and six months post insertion. Findings indicate a significant reduction in total cholesterol with a significant increase in total haemoglobin and BMI. However there was no significant change noted in the fasting blood sugar, glycosylated haemoglobin, systolic blood pressure and diastolic blood pressure.